Studi Komparatif Sistem Pendidikan di Korea Selatan Dengan Indonesia - Matilda Moniz; Taufik Muhtarom (Journal Innovation In Education, 2024)
Comparative studies have two syllables, consisting of "study" and "comparative". In the large Indonesian dictionary, the word "study" is a study, research or analysis. Meanwhile, the meaning of the word "comparative" is to compare. In this comparative research, it is usually used to compare the similarities or differences of a fact or the nature of the research object which is based on the research framework. The type of research used is a qualitative research method through a literature review (Kartiningrum, 2016). Qualitative research refers to the thoughts, feelings, opinions or beliefs of the person being studied and cannot be measured quantitatively (Ulfatin, 2022). The data used to prepare this work came from various articles related to the topics discussed. The social studies curriculum in South Korea began in 1946, when South Korea was liberated from Japanese colonial rule and came under the United States military. The main aim of this curriculum is to eradicate the remnants of Japanese imperialism. The curriculum in Indonesia has changed many times since independence. Since 2013/2014, Indonesia has begun implementing the 2013 Curriculum in schools in Indonesia for grades 1, 4, 7 and 10. The implementation of the 2013 curriculum will be carried out in stages until it is implemented in all classes in Indonesia. In 2020 in South Korea there will be an additional curriculum, namely the curriculum local content as well as in Indonesia. Comparative studies between the education systems in South Korea and Indonesia reveal striking differences in educational approaches, quality and outcomes. South Korea is known for its focus on quality education with high standards and a competitive learning culture, while Indonesia often places more emphasis on equal access to education throughout the region.